Baseline distribution of petroleum hydrocarbon contamination in the marine environment around the coastline of Qatar. (March 2023) - Al-Shamary, Noora; Hassan, Hassan; Leitão, Alexandra; Hutchinson, Simon M.; Mondal, Debapriya; Bayen, Stéphane
Abstract: Levels of organic contaminants (TPHs, PAHs) were simultaneously determined in both abiotic (sediments, seawater) and biotic ( Pinctada radiata oysters) samples at four sites along the coastline of Qatar (Arabian Gulf) in 2017–2018. TPHs and PAHs were more frequently detected in oyster tissues than sediment and seawater samples collected from the same areas. While levels of TPHs and PAHs in seawater and sediments were lower than previous local studies and worldwide studies, PAHs levels observed in pearl oyster tissue (25.9–2240 μg/kg) were relatively higher than in previous studies in Qatar. In general, eight PAHs compounds were detected in oyster tissue, with benzo( a )pyrene displaying the highest concentration. The coast of Qatar could be affected by seasonal patterns of pollutants, where TPHs and PAHs levels increased in winter compared to summer. These results provide key information on the use of the pearl oyster as a bioindicator species and Qatar's marine environment. Highlights: TPHs and PAHs were measured in sediments, seawater and oysters in Qatar. TPHs and PAHs were more frequently detected in oysters than abiotic samples. Benzo( a )pyrene was the most prevalent PAH in oyster tissues. TPHs and PAHs levels increased in winter compared to summer.